The impact of the professional skepticism behavior of the external auditor on the improve quality of information content of the report :: Study of governors accounts at Tebessa - RAIS, Sofiane; ZAYBET, Noureddine (Journal of Human Sciences, 2020)
This study aims at demonstrating the impact of the professional skepticism in the external audit, on the improve quality of information content of the report. To achieve the objectives of the study and answer its questions the questionnaire was designed to collect the information, it was distributed to governors accounts in tebessa, and its analysis by the statistical program SPSS. The study has concluded that there is an impact and relationship with a ststistically significant between professional skepticism and quality of information content of the report.